2016
DOI: 10.1177/0040517516632480
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of stretch and recovery properties of woven stretch fabrics

Abstract: Stretch woven fabrics are widely used owing to their comfortable properties such as formability, fitting to the human body and shape retention after wearing. These distinguishing properties are determined by stretch and recovery tests. The aim of this study is to determine the optimum elastane draw ratio, load and relaxation type for best stretch and recovery properties of woven stretch fabrics. An optimization model is developed to determine the optimum draw ratio of the elastane core in the yarn, load applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 2 publications
2
20
0
4
Order By: Relevance
“…Tüm streç dokuma kumaşlarda olduğu gibi streç denim kumaşların streçlik ile geri toparlanabilme yetenekleri çok önemlidir. Buradaki streçlik özelliği kumaşın insan vücuduna göre şekil alabilmesini, geri toparlanabilme özelliği de yorulma davranışı sonrası estetik görünümü etkilemektedir [36].…”
Section: Denim Kumaşların Spesifikasyonlarıunclassified
“…Tüm streç dokuma kumaşlarda olduğu gibi streç denim kumaşların streçlik ile geri toparlanabilme yetenekleri çok önemlidir. Buradaki streçlik özelliği kumaşın insan vücuduna göre şekil alabilmesini, geri toparlanabilme özelliği de yorulma davranışı sonrası estetik görünümü etkilemektedir [36].…”
Section: Denim Kumaşların Spesifikasyonlarıunclassified
“…Desirability method makes use of an objective function, D(X), called the desirability function. This function reflects the desirable ranges for each response (d i ) and desirable ranges changes from 0 to 1 which corresponds least to most desirable and involves the use of a geometric mean of individual desirability [23][24][25]. For various responses and factors, all targets are combined as a desirability function.…”
Section: Quality Optimizationmentioning
confidence: 99%
“…Weights greater than 1 (maximum weight is 10), give more emphasis to the goal. Weights less than 1 (minimum weight is 0.1), give less emphasis to the goal [23]. Desirability curves for goal is maximum, minimum and within the range is illustrated in figure 6.…”
Section: Quality Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides a better understanding the effect of sheath fibres, core filament and yarn finenesses on dual-core yarns. In addition, majority of the studies reported in the literature has focused on the usage of cotton fibre as a sheath fibre for core-spun yarns composed of single [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and dual core filaments [1][2][3][4]. Present study was therefore undertaken to investigate the effect of different sheath fibre types on dual-core yarns.…”
Section: Introductionmentioning
confidence: 99%